2007
DOI: 10.1007/s10549-007-9734-1
|View full text |Cite
|
Sign up to set email alerts
|

I171V germline mutation in the NBS1 gene significantly increases risk of breast cancer

Abstract: Nijmegen Breakage Syndrome (NBS) is a rare autosomal, recessive disease caused by homozygous mutations in the NBS1 gene. The most common deletion of 5 bp (657del5) in exon 6, which affects mostly the population of Central Europe is observed. Among the typical features of this disorder is that NBS patients experience a high incidence of lymphoid malignancies as well. An increased risk of solid tumors development for 657del5 carriers was the reason to investigate the role of NBS1 gene as a susceptible one for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
(36 reference statements)
0
35
0
Order By: Relevance
“…Mutant NBS1 carriers have a 3-fold to 9-fold increased risk of breast cancer, although this varies with ethnic background (18,19). Moreover, epidemiologic studies have indicated that a reduced expression of NBS1 is observed in up to 80% of breast cancer cases without any reported mutations (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant NBS1 carriers have a 3-fold to 9-fold increased risk of breast cancer, although this varies with ethnic background (18,19). Moreover, epidemiologic studies have indicated that a reduced expression of NBS1 is observed in up to 80% of breast cancer cases without any reported mutations (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…NBS1 mutant carriers also have a high risk for solid tumors, including breast cancer (18)(19)(20). Cells derived from such patients show defects in cellular responses to the presence of DNA doublestrand breaks (DSB), such as homologous recombination repair (21,22) and an abnormal regulation of checkpoints (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed that the germline p.I171V mutation in NBN, one of the M/R/N genes, may be considered as a risk factor in the development of solid malignant tumor including breast cancer, larynx and colorectal cancer [3][4][5] or acute lymphoblastic leukemia [6]. Heterozygous carriers of the NBN c.657del5 mutation have an increased risk of malignant tumor development, especially of breast cancer [7,8], prostate [9], and colon and rectal cancer [7].…”
Section: To the Editormentioning
confidence: 99%
“…The DNA isolation procedure was described in our previous study [3]. The research protocol was approved by the ethics committee, Poznan University of Medical Sciences and all patients signed the informed consent form.…”
Section: To the Editormentioning
confidence: 99%
“…To date, the NBS1-I171V polymorphic variant was detected frequently only in Polish patients with breast cancer, head and neck cancer, and colorectal cancer (25)(26)(27)(28). However, other groups did not find a similar association in European patients with breast cancer, leukemia, or lymphoma (29)(30)(31).…”
Section: Nbs1-i171v Polymorphic Variant Increases the Risk Of Breast mentioning
confidence: 99%